Analisis dan Perancangan Sistem Informasi Hollowframe Berbasis Website Menggunakan Metode Waterfall untuk Meningkatkan Manajemen Data - Afif Rifai Nimal Abdu; Benaya Chessa Sarmanela; Manase Rezata Purba; Shalom Amadeo Muryanto (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the workflow of a digital product purchasing system, focusing on the user login process, admin verification, and product access after payment. The system involves three key actors: the buyer, the system, and the admin, each playing a crucial role in ensuring the security and continuity of transactions. The workflow is designed to minimize transaction errors, ensure data validity, and improve operational efficiency and security in managing digital products. The study employs flowcharts and Unified Modeling Language (UML) diagrams to visually represent the interactions between these actors and the system. The analysis begins with the user login process, where the buyer provides authentication credentials, followed by admin verification to ensure authorized access. Once the payment is processed, the system verifies the transaction and grants the buyer access to the digital product. Each step is mapped using flowcharts to depict the sequential actions and decision points within the system, while UML diagrams provide a more detailed view of system architecture and interactions. The findings reveal that the system is designed to mitigate errors through structured validation and secure data handling, enhancing the overall purchasing experience. Additionally, the admin's role is critical in overseeing transaction approval and ensuring that digital products are accurately delivered. The study highlights the importance of system design in supporting smooth transactions, fostering user trust, and maintaining high levels of security. This analysis is valuable for improving the design and performance of digital product purchasing systems in various e-commerce settings.